Toll-Like Receptor Signaling Contributes to Proinflammatory Mediator Production in Localized Provoked Vulvodynia. Issue 1 (January 2018) - Falsetta, Megan L.; Foster, David C.; Woeller, Collynn F.; Pollock, Stephen J.; Bonham, Adrienne D.; Piekna-Przybylska, Dorota; Maggirwar, Sanjay B.; Haidaris, Constantine G.; Phipps, Richard P.
Abstract : Objectives: Localized provoked vulvodynia (LPV) afflicts approximately 8% of women in the United States and represents a huge financial, physical, and psychological burden. Women with LPV experience intense pain localized to the vulvar vestibule (area immediately surrounding vaginal opening). We have identified mechanisms involved in the development of LPV whereby vulvar fibroblasts respond to proinflammatory stimuli to perpetuate an inflammatory response that causes pain. However, these mechanisms are not fully elucidated. Therefore, we explored the role of toll-like receptors (TLRs), a class of innate immune receptors that rapidly respond to microbial assaults. Materials and Methods: To determine whether TLRs are expressed by vulvar fibroblasts and whether these contribute to proinflammatory mediator production and pain in LPV, we examined TLR expression and innate immune responses in fibroblasts derived from painful vestibular regions compared with nonpainful external vulvar regions. Results: Human vulvar fibroblasts express functional TLRs that trigger production of inflammatory mediators associated with chronic pain. We focused on the TLR-7–imiquimod proinflammatory interaction, because imiquimod, a ligand of TLR-7, may exacerbate pain in women during treatment of human papillomavirus–associated disease. Conclusions: Human vulvar fibroblasts express a broad spectrum of TLRs (a new finding). A significantly higher TLR-mediated proinflammatory response was observed in LPV case vestibular fibroblasts, and with respect to the imiquimod-TLR 7 interaction, development of chronic vestibular pain and inflammation may be a possible sequelae of treatment of vulvar human papillomavirus–associated disease. Suppressing enhanced TLR-associated innate immune responses to a spectrum of pathogen-associated molecular patterns may represent a new/effective therapeutic approach for vulvodynia. Abstract : Toll-like signaling is involved in the heightened proinflammatory responses in the vestibule of women with localized provoked vulvodynia and could represent a new therapeutic target.